You need to replace 0 for x to evaluate the limit, such that:

`lim_(x->0) (sin x)^tan x = (sin 0)^(tan 0) = 0^(0) = 0`

The indetermination `0^0` requests for you to use l'Hospital's theorem, such that:

`lim_(x->0) (sin x)^tan x = lim_(x->0) e^(ln (sin x)^tan x)`

Using power property of logarithms yields:

`lim_(x->0) e^(ln...

(The entire section contains 197 words.)

## Unlock This Answer Now

Start your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

**Further Reading**